PENDEKATAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN BERDASARKAN KONSEP DARUL AHDI WA SYAHADAH - Muhammad Salisul Khakim (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
This study aims to formulate the Pancasila and Citizenship Education curriculum as compulsory university courses in Islamic tertiary institutions, such as universities under the Muhammadiyah Islamic Community Organization foundation. The Pancasila Ideology assessment organization is in line with Islamic values, namely declaring the concept of the Pancasila State as Darul Ahdi wa Syahadah. This concept also needs to be internalized into the educational curriculum as a learning medium to introduce the relationship between the Pancasila Ideology and the Islamic Religion. This research uses a qualitative approach, with data sources through thorough observation techniques and in-depth interviews related to the research object. This research is also equipped with secondary data sources, namely literature studies in the form of books, journals, and documents related to education and the Pancasila ideology as well as Islamic values in view. This research shows that Muhammadiyah College needs to form a modernist and reformist educational framework, which is able to build Muhammadiyah ideology by maintaining the nationalism of the Indonesian nation which is based on the state ideology through the education system.